The Dual Role of a Single Parent as Breadwinner and Caregiver: A Case Study of a Teacher at Darunnajah Islamic Boarding School, Jakarta - Rohayana, Ade Dedi; Marzuqi, M Ali; Abdurrahman Wahid, (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2025)
This study aims to comprehensively examine the dual roles carried out by female single parents who work as teachers in the Darunnajah Islamic Boarding School, Jakarta. This phenomenon is a crucial subject in Islamic family law and educational sociology, as women in such conditions are not only responsible for meeting the economic needs of their families but also serve as the primary caregivers for their children. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that single-parent teachers in pesantren face complex challenges, including psychological stress, time constraints, and limited financial resources. However, they manage to balance these dual roles relatively well, supported by institutional flexibility, effective time management strategies, and personal spirituality. The study highlights the importance of affirmative policies in Islamic educational institutions that are inclusive toward the needs of single-parent teachers. Furthermore, this article recommends stronger collaboration between state and religious educational institutions to provide social protection and proper education for children from incomplete families.